Identification of New Peptide Biomarkers for Bacterial Bloodstream Infection. Issue 2 (10th December 2019) - Ma, Yating; Wen, Xinyu; Kong, Yi; Chen, Chen; Yang, Ming; He, Shang; Wang, Jianan; Wang, Chengbin
Abstract : Purpose: Due to a lack of effective early diagnostic measures, new diagnostic methods for bacterial bloodstream infections (BSIs) are urgently needed. A protein–peptide profiling approach can be used to identify novel diagnostic biomarkers of BSIs. Experimental design: In this study, MALDI‐TOF MS and nano‐LC/ESI‐MS/MS are used to analyze serum peptides. In addition, GO and network analyses are conducted as a means of analyzing these potential protein markers. Finally, the potential biomarkers are verified in independent clinical samples via ELISA. Results: m / z 1533.8, 2794.3, 3597.3, 5007.3, and 7816.7 reveal an identical trend; the intensity of m / z 1533.8, 2794.3, and 3597.3 are higher in the infection group relative to controls, whereas the intensity of m / z 5007.3 and 7816.7 are lower in the infection group. Four peaks are successfully identified including ITIH4, KNG1, SAA2, and C3. GO and network analyses find these proteins to form an interaction network, which may be correlated with BSI. ELISA results indicate that ITIH4, KNG1, and SAA2 are effective in differentiating infected from normal control group and the febrile group. Conclusions and clinical relevance: These biomarkers have the potential to offer new insights into the signaling networks underlying the development and progression of BSI.